The Reality of Job Satisfaction for Physical Education Teachers in the General Directorate of Anbar Education from Their Point of View - Yaseen Ali Khalaf (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The research aims to identify the level of job satisfaction among physical education teachers in the General Directorate of Anbar Education, as the researcher used the descriptive approach for its suitability and the nature of the research problem, the research community was represented by (380) teachers in the General Directorate of Anbar Education, as for the research sample, it was divided into a sample of the exploratory experience (60) teachers with a percentage of (15.78%) and the main experiment sample (320) teachers and a percentage of (84.21%) of the total research community, and the researcher concluded that the scale proved effective to measure the variable of job satisfaction For physical education teachers in the General Directorate of Anbar Education from their point of view and obtaining all areas of the job satisfaction scale on high and close grades and according to the answers of the sample except for the last field, and the researcher recommended the need to pay attention to physical education teachers through the development of material and moral incentives for creative ones to satisfy their needs to achieve job satisfaction and work to activate the physical education lesson in schools and the diversity of its activities and events and provide professional and educational needs.